1986
DOI: 10.1128/jcm.24.5.716-720.1986
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Campylobacter pyloridis in patients with antrum gastritis and peptic ulcers by culture, complement fixation test, and immunoblot

Abstract: The association of Campylobacter pyloridis with antrum gastritis and peptic ulcers was described. We investigated antral biopsies from 180 patients who underwent gastroscopy. By culture or Gram stain or both, we found overall 98 (54%) of them to be positive for C. pyloridis. In the various groups the following percentages were found to be positive: normal antral mucosa 3% (n = 30); moderate superficial antrum gastritis, 49% (n = 83); severe superficial antrum gastritis, 86% (n = 44); duodenal ulcer, 83% (n = 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
35
0
2

Year Published

1988
1988
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(43 citation statements)
references
References 18 publications
6
35
0
2
Order By: Relevance
“…The matched odds ratio in all sets was 3.23, with a 95% confidence interval of 1.95–5.35 (the p ‐value obtained using the Mantel‐Haenszel test was 0.001), showing a strong association between the development of GU after the earthquake and seropositivity for H. pylori infection in uninjured patients. The seroprevalence of H. pylori infection and the odds ratio of the cases were similar to those of patients whose GUs were unrelated to the earthquake, as reported previously [22–24]. Indeed, we observed that the seroprevalence of H. pylori infection in the GU cases that developed during the corresponding period of the previous year (1994) in the same hospitals was 82.3% (237/288), which was not significantly different from that of the GUs that occurred after the earthquake (134/166, 80.7%).…”
Section: Resultssupporting
confidence: 88%
“…The matched odds ratio in all sets was 3.23, with a 95% confidence interval of 1.95–5.35 (the p ‐value obtained using the Mantel‐Haenszel test was 0.001), showing a strong association between the development of GU after the earthquake and seropositivity for H. pylori infection in uninjured patients. The seroprevalence of H. pylori infection and the odds ratio of the cases were similar to those of patients whose GUs were unrelated to the earthquake, as reported previously [22–24]. Indeed, we observed that the seroprevalence of H. pylori infection in the GU cases that developed during the corresponding period of the previous year (1994) in the same hospitals was 82.3% (237/288), which was not significantly different from that of the GUs that occurred after the earthquake (134/166, 80.7%).…”
Section: Resultssupporting
confidence: 88%
“…Studies with low (arbitrarily defined as <90%) prevalence of H. pylori infection in DU patients were chosen (Table 3). 10, 13, 17, 25, 26, 27–30, 32, 33, 35, 37, 40–43, 49, 50, 52, 53, 56–58, 61, 62, 65, 66, 68, 69, 71–73, 75–81, 104, 148, 149, 164, 190–198, 199, 200 The following variables were extracted, with the intention to explain the low prevalence of the infection in these studies: year of publication, nationality of the authors, study design, number of patients included, prevalence of H. pylori infection, percentage of NSAID use in H. pylori ‐negative DU patients, prevalence of H. pylori in DU after excluding NSAIDs, diagnostic methods used (and definition of H. pylori positivity), location of biopsy samples (antrum, body or both), exclusion of patients with previous PPIs or antibiotic use, or with bleeding DU and finally, age of population (children or adults).…”
Section: Studies With Low (<90%) Prevalence Of Helicobacter Pylori Inmentioning
confidence: 99%
“…Since the initial implication of Helicobacter pylori in the etiology of gastroduodenal disease by Warren and Marshall in 1983 [1], further evidence has established the association of this spiral bacterium with active chronic gastritis, duodenal ulcer, gastric ulcer, and perhaps non-ulcer dyspepsia in adults [2][3][4][5][6]. The role of H. priori in the latter syndrome remains controversial [7].…”
Section: Introductionmentioning
confidence: 99%